1985
DOI: 10.1152/ajpheart.1985.249.2.h321
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-dependent hypertension produced by chronic central angiotensin II infusion

Abstract: Experiments were performed to characterize the hypertension produced by chronic intracerebroventricular (ICV) infusion of angiotensin II (ANG II) in conscious rats. Infusion of ANG II into a lateral cerebral ventricle for 5 days (1 or 6 micrograms/h) produced dose-dependent increases in mean arterial pressure associated with increased water intake. No consistent changes in heart rate, urinary electrolyte excretion, or water balance were observed. Similarly, no alterations in plasma sodium and potassium concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
3
15
4
Order By: Relevance
“…It must be considered that at least part of the effect of central ANG II administration to influence splenic cytokine gene expression may have resulted from ANG II leaking from the cerebrospinal fluid into the peripheral circulation and causing norepineprine release from adrenergic nerve ending sites. Although the present data do not exclude this possibility, it seems unlikely on the basis of the results of Bruner et al (7), who reported that plasma ANG II levels were not increased during the 5th day of a chronic intracerebroventricular infusion of ANG II administered in the microgram dose range. In contrast, the present study used a single 10-min central infusion of a dose of ANG II in the nanogram range.…”
Section: Discussioncontrasting
confidence: 75%
“…It must be considered that at least part of the effect of central ANG II administration to influence splenic cytokine gene expression may have resulted from ANG II leaking from the cerebrospinal fluid into the peripheral circulation and causing norepineprine release from adrenergic nerve ending sites. Although the present data do not exclude this possibility, it seems unlikely on the basis of the results of Bruner et al (7), who reported that plasma ANG II levels were not increased during the 5th day of a chronic intracerebroventricular infusion of ANG II administered in the microgram dose range. In contrast, the present study used a single 10-min central infusion of a dose of ANG II in the nanogram range.…”
Section: Discussioncontrasting
confidence: 75%
“…In a previous study, the continuous ICV infusion of angiotensin II caused salt-sensitive hypertension in rats. 21 Together, these findings indicate that the genesis of hypertension in saltinduced hypertensive models such as DOCA-salt hypertension through the upregulation of the brain renin-angiotensin system genes involves not epithelial sodium channels, as previously reported, 22 but rather newly cloned amiloridesensitive sodium channels in the brain that are activated by FMRFamide. 6 FMRFamide-activated brain sodium channel may participate in the upregulation of the brain renin-angiotensin system genes.…”
Section: Discussionsupporting
confidence: 74%
“…8,10 Physiological interactions are also observed, such as Ang-mediated drinking and vasopressin responses, sodium-induced potentiation of the pressor action of Ang, and angiotensinergic modulation of the response to dehydration. [11][12][13][14] The question that has arisen is the role of the specific AT1 subtypes in the responses. Autoradiographic techniques used to measure receptor density do not distinguish between AT1a and AT1b subtypes because of the structural similarity of the receptors.…”
mentioning
confidence: 99%